Professionally Social Using social media for professional research communication - Klarstrup, Lisbeth (Language at Work - Bridging Theory and Practice, 2009)
In this short article, I will discuss what I consider the important characteristics, opportunities and challenges offered by social media when used for professional communication purposes. The insights – or perhaps rather points of discussion - put forth here are based on my own experiences as practicing social media communicator and Danish research blogger, as well as on my general research into the use of social media for professional communication purposes, by for instance Danish politicians (see Klastrup and Svejgaard Pedersen 2005, Klastrup 2007).